Implementasi Metode Action Research untuk Peningkatan Daya Saing Umkm Melalui E-Commerce - Azizah Zakiah; Ardhian Ekawijana; Eka Angga Laksana (BPSDMP Kominfo Manado, 2019)
Bandung city has Binong Jati knitting textile center established since 1965. This region is famous to neighboring countries because its knitted products are exported to Singapore, Brunei Darussalam, and Malaysia. Wanina Store and Karimake Store is a production house located in Binong Knitting Village. Production capacity has decreased significantly due to decreased sales volume so that it affects the level of business profits and impact on the low level of production. These SMEs are still using conventional ways in marketing their products and their knowledge in innovating technology is still low. Both partners are still using traditional marketing methods. They have not taken advantage of the existing marketplace or social media, due to the level of skills in the mastery and utilization of information technology is very low. So, the solution to the problem is (1) create an e-Commerce-based website to increase market share expansion and sales management. (2) provide training on the use of e-commerce that has been made. (3) provide training on the utilization of top 5 popular. The research method used in this research is the action research method and to measure the success of the system that has been implemented using the DeLone & Mc lean framework.Keywords : Action Research, SMEs, e-commerce, Improving, DeLone &Mc Lean.